A retrospective analysis of mid trimester termination of pregnancies for fetal congenital malformations at tertiary care hospital - Suriyanarayanan, Geethalakshmi; Kandasamy, Vijayalakshmi; Ramachandran, Anuradha Coimbatore (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: This study was conducted to analyse the spectrum of fetal anomalies as a cause of pregnancy termination in a tertiary care hospital. Methods: This retrospective study includes antenatal women with fetal anomalies diagnosed by an ultrasound (USG) and admitted in Chettinad Hospital and Research Institute, Kelambakkam from January 2018 to January 2020 for termination of pregnancy. Data was collected from hospital records and analysed. Results: Gestational age of women with fetal congenital anomalies ranged from 13 to 21 weeks. Pregnancy termination, was performed between 17-19 weeks of gestation in 41% of patients, between 13-15 weeks and 19-21 weeks in 23% of women respectively. Congenital fetal anomalies resulting in termination of pregnancy were CNS, musculoskeletal, cardiovascular, renal and multiple anomalies. CNS abnormalities was a major cause of termination of pregnancy which includes meningomyelocele, spina bifida, acrania, anencephaly. Conclusions: In our study conducted at our tertiary care center, CNS abnormalities were the major cause of mid trimester termination of pregnancies, followed by musculoskeletal abnormalities being second most common cause.